PENINGKATAN KAPASITAS PENGUSAHA SEPATU DAN TAS KULIT DI MALANG UNTUK TEMBUS PASAR LUAR NEGERI - Istutik, '; Bunyamin, ' (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
IbM Program for Shoes & Bags Leather Manufacturers in Malang aims to increase the capacity of them who are economically productive community groups. Their problems are (1) lack of ability in managing production schedule so often can not serve the consumer on time, lack of ability to determine the cost of product so that the selling price is not standard, lack of ability to market product which only relies on buyer/reseller, and limited production capacity. The method of implementing the program to solve partner problems is to provide various training, then proceed with mentoring. Sewing machine equipment is provided to increase production capacity. The output target of the program is to increase total sales and partner's revenue. Impacts of program execution have increased production capacity, increased sales and earnings turnover, enhanced communication capabilities of partners, diversity of marketing media and successful to compete overseas market.